ANALISIS PENGARUH KOMPETENSI APARAT DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN DANA (Studi Pada Desa di Kecamatan Majalengka): (Studi Pada Desa di Kecamatan Majalengka) - eli Achmad Mahiri; Latief Z Nur (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Success in managing village finances cannot be separated from good village management accountability. Fund management accountability needs to be supported through the competence of the apparatus and community participation to build a better village. This study aims to determine the effect of apparatus competence and community participation on the accountability of fund management in Majalengka District. The research population was all village officials in Majalengka District, amounting to 235 people. The research sample amounted to 100 samples with proportional random sampling technique. The type of data in this study is qualitative which is quantified (scoring), with a Likert measurement scale. Source of primary data, obtained from the distribution of questionnaires. The analysis tool uses descriptive analysis and verification. The verification analysis includes classical assumption test, multiple linear regression, model feasibility test, coefficient of determination and hypothesis testing with independent variables consisting of apparatus competence and community participation, and the dependent variable is Fund Management Accountability. The results of this study indicate that the competence of the apparatus has a significant effect on the accountability of fund management. Community participation has a significant effect on fund management accountability